2018
DOI: 10.1007/s40257-018-0381-6
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Conceptual Model of the Experience of Chronic Itch in Adults

Abstract: Our conceptual model demonstrates the profound patient-burden of itch and identifies unmet needs in the evaluation and management of itch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 26 publications
3
38
0
Order By: Relevance
“…PIQ items were developed and content validity was established as part of a broader conceptual model of itch using mixed methods, including systematic review ( n = 491 manuscripts) and semistructured interviews ( n = 33 adults with chronic itch with multiple aetiologies as previously described) 8. After item development, content validity was confirmed in AD using cognitive debriefing interviews in five adults with AD (Table 1 and File S1; see Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…PIQ items were developed and content validity was established as part of a broader conceptual model of itch using mixed methods, including systematic review ( n = 491 manuscripts) and semistructured interviews ( n = 33 adults with chronic itch with multiple aetiologies as previously described) 8. After item development, content validity was confirmed in AD using cognitive debriefing interviews in five adults with AD (Table 1 and File S1; see Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…5 Itch is a burdensome symptom with complex interactions between disease-specific and environmental factors and baseline characteristics. 16 Many adults with AD reported that AD limited their lifestyle (51.3%), caused them to avoid social interaction (39.1%), and impacted their activities (43.3%); they had only fair or poor overall health (25.8%) and were somewhat or very dissatisfied with life (16.7%). 5 These effects occurred even in mild AD, but even more so in moderate and severe AD.…”
Section: Burden Of Admentioning
confidence: 99%
“…Although conceptual models detailing pediatric AD and pruritus exist in the published literature, to our knowledge, this study was the first of its kind to explore the lived experience of AD in both adult and adolescent patients. 16,17 In addition, to our knowledge, this is the first qualitative study to document the lived experience of AD in adolescents separately from other pediatric populations. Typically, research with adolescents (aged 11–17 years) is combined with that with younger pediatric patients (aged 0–10 years), for whom the HRQoL implications of AD are quite different.…”
Section: Discussionmentioning
confidence: 99%